Hubungan Minat Belajar dengan Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa Kelas X SMK - Rona Nasywa Muhadzdzib; Mochamad Ridwan (MAN Insan Cendekia Jambi, 2026)
Physical Education and Health has learning outcomes for students, one of which is healthy and clean living habits, and there is one factor that influences it, namely the student's interest factor. The condition of students who lack understanding about health so that PHBS must be implemented so as not to affect the quality of life. Interest and health factors may influence these learning outcomes. The study is designed to look at how students' interest in learning PJOK relates to their habits of living cleanly and healthily. It is hoped that the findings will offer useful suggestions, making the learning of PJOK more effective for students. It was conducted using a quantitative method and conducting research through correlations. Sampling using cluster random sampling techniques and drawing lots, so that the sample numbered 104 students, and using a closed questionnaire with a Likert scale as an instrument. The results of data analysis with quantitative descriptive statistics showed that students' interest in learning physical education and health was in the moderate category (46.2%) with students' PHBS being sufficient (32.7%). Additionally, the study findings were assessed using the Pearson product moment correlation test and indicated no discernible association between the variables under investigation. interest in learning physical education and health with clean and healthy living behaviors p = 0.099 (p>0.05). Interest in learning PJOK is not directly related to PHBS, but there needs to be guidance regarding this behavior in PJOK learning, because it can help improve clean and healthy living behavior in class X students at SMK Negeri 1 Duduksampeyan.